Circ0085539 Promotes Osteosarcoma Progression by Suppressing miR-526b-5p and PHLDA1 Axis - Liu, Pengcheng; Liu, Wei; Gao, Hang; Zhang, Yuanding; Yan, Ming; Wang, Xu (Frontiers in Oncology, 2020)
Background: We have previously found that circ0085539/miR-526b-5p axis participated in the progression of osteosarcoma (OS). We have been interested in expanding the networking involving circ0085539 and miR-526-5p. We identified another critical downstream target of this axis, PHLDA1, thus intending to uncover the interaction between the axis and PHLDA1. Methods: Live imaging of mice tumor xenografts was conducted. Immunohistochemistry (IHC) and H&E staining was performed for our in vivo experiment, while the CCK-8 assay, flow cytometry, wound healing, Transwell invasion and clone formation were employed to assess cellular biological functions. Results: Circ0085539 was firstly found upregulated in osteosarcoma tissues and cell lines, and circ0085539 knockdown obviously suppressed proliferation and induced apoptosis. Subsequently, miR-526b-5p functionally attenuated the tumor suppressive effects induced by circ0106714 silencing on OS cells. PHLDA1 silencing significantly led to proliferation suppression, apoptosis induction as well as the inhibition of migration, invasion and colony formation capabilities in OS cells, which also could be restored by miR-526b-5p inhibitor. Conclusion: Taken together, circ0085539 effectively promoted progression of osteosarcoma through sponging miR-526b-5p to release PHLDA1, strongly suggesting that in vivo intervention of circ0085539-miR-526b-5p-PHLDA1 axis could function as a promising OS-targeted therapy.